2018
DOI: 10.1039/c7nj05176j
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cu2+-specific “Turn-ON” fluorescent probe based on [5]helicene with very large Stokes shift and its potential application in living cells

Abstract: The sensor provides Cu2+-sensitive with low detection limit and very large Stokes shift, and can induce the emission in the HepG2 cellular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The performance of sensor A (FWA‐DTI complex) is comparable with other reported fluorescence‐based probes for Cu 2+ (Table ). Unlike many probes reported in the literature, the approach introduced herein produces 100% water‐soluble Cu 2+ sensors. The main advantage of the approach described in this work however, is its simplicity; it enables sensor assembly via single‐step mixing of inexpensive commercial materials, which circumvents the multistep synthesis and purification involved in the production of current Cu 2+ sensors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of sensor A (FWA‐DTI complex) is comparable with other reported fluorescence‐based probes for Cu 2+ (Table ). Unlike many probes reported in the literature, the approach introduced herein produces 100% water‐soluble Cu 2+ sensors. The main advantage of the approach described in this work however, is its simplicity; it enables sensor assembly via single‐step mixing of inexpensive commercial materials, which circumvents the multistep synthesis and purification involved in the production of current Cu 2+ sensors.…”
Section: Resultsmentioning
confidence: 99%
“…While sensor A has many advantages, it has some notable disadvantages. Sensor A is a “turn‐off” probe for Cu 2+ and thus has a lower signal‐to‐noise ratio than the “turn‐on” probes in Table . In addition, the noncovalent nature of sensor A makes it more susceptible to interference [Figures (e,f)], thus limiting its use to applications where interfering species can be easily removed, such as water quality monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…The sensor selectively detected Cu 2+ ions. The detection limit was 2.6 ppb [ 53 ]. Udhayakumari et al found that 2,3-diaminophenazine, 1,2-diamino-anthraquinone, and 2,4-dinitrophenylhydrazine could work as fluorescent probes for Cu 2+ ion selective detection.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Copper (Cu 2 + ) ranks as the third most plentiful cations in our body and has some critical roles in a variety of biological activities. [2][3][4][5] Cu 2 + functions to produce red blood cells and acts as a cofactor of various enzymes like ferroxidases and cytochrome oxidase. [6,7] Cu 2 + stays in the ecological system indefinitely because of its non-biodegradability, and so it can be a huge menace for human safety and health.…”
Section: Introductionmentioning
confidence: 99%